Suicide during Perinatal Period: Epidemiology, Risk Factors, and Clinical Correlates - Orsolini, Laura; Valchera, Alessandro; Vecchiotti, Roberta; Tomasetti, Carmine; Iasevoli, Felice; Fornaro, Michele; De Berardis, Domenico; Perna, Giampaolo; Pompili, Maurizio; Bellantuono, Cesario (Frontiers in Psychiatry, 2016)
Perinatal period may pose a great challenge for the clinical management and treatment of psychiatric disorders in women. In fact, several mental illnesses can arise during pregnancy and/or following childbirth. Suicide and infanticide have been considered relatively rare events during the perinatal period. However, in some mental disorders (i.e. postpartum depression, bipolar disorder, postpartum psychosis, etc.) have been reported a higher risk of suicidal ideation, suicide attempt or suicide. Therefore, a complete screening of mothers’ mental health should also take into account thoughts of suicide and thoughts about harming infants as well. Clinicians should carefully monitor and early identify related clinical manifestations, potential risk factors and alarm symptoms related to suicide. The present paper aims at providing a focused review about epidemiological data, risk and protective factors and an overview about the main clinical correlates associated with the suicidal behaviour during the pregnancy and postpartum period.